2008
DOI: 10.1016/j.archoralbio.2008.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Protection of short-time enamel erosion by different tetrafluoride compounds

Abstract: OBJECTIVE: This in vitro study aimed to analyse the protective effect of differently concentrated titanium (TiF(4)), zirconium (ZrF(4)) and hafnium (HfF(4)) tetrafluoride on enamel erosion. METHODS: Polished enamel surfaces of 36 bovine crowns were covered with tape leaving 4 enamel windows each 3mm in diameter exposed. The crowns were randomly assigned to six groups (each n=6) and pretreated with 4% TiF(4), 10% TiF(4), 4% ZrF(4), 10% ZrF(4), 4% HfF(4) or 10% HfF(4) for 4 min (first window), 10 min (second win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 21 publications
0
22
0
10
Order By: Relevance
“…Due to these findings, a more patient independent approach seems to be desirable. Furthermore, the durability of the anti-erosive effect of topically applied fluorides or the above mentioned new agents are limited, ranging from a few seconds (75 s) [18] up to few minutes (3.5 -18 min) [12,19] after a single application.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these findings, a more patient independent approach seems to be desirable. Furthermore, the durability of the anti-erosive effect of topically applied fluorides or the above mentioned new agents are limited, ranging from a few seconds (75 s) [18] up to few minutes (3.5 -18 min) [12,19] after a single application.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, TiF 4 action has been widely studied 19,[28][29][30] in Dentistry. In the form of TiF 4 , this fluoride presents satisfactory stability and particular mechanism of action in relation to the other fluorides.…”
Section: Titanium Tetrafluoridementioning
confidence: 99%
“…Since TiF 4 enables the formation of this acid-resistant layer, it is responsible for the production of a diffusion barrier and a reservoir of F ions, which may delay the dissolution of dental tissue exposed to acidic challenges 25 . For this reason, its effect on erosion has been studied and has obtained promising results in both enamel 19,20,30,39,42 and dentin 43 . These results are dependent on the concentration, form of presentation, pH and time of application of TiF 4 26,30,39 .…”
Section: Titanium Tetrafluoridementioning
confidence: 99%
See 1 more Smart Citation
“…Thereby, ZrCl lead to the formation of a relatively thick surface coating, while titaniumchloride pretreatment showed a thinner and fragile surface coating (Clarkson et al, 1984). Thus, it can be speculated that HfF 4 and ZrF 4 application might also lead to a mechanical protection of dental hard tissues the enamel surface, which shows a similar mode of action as the TiF 4 glaze-like layer (Wiegand et al, 2008a). Moreover, it is suggested that the protective effect of HfF 4 and ZrF 4 might also due to act chemical interaction with the apatite, as it is known that metal ions lead to an increased fluoride retention due to their ability to complex with fluoride.…”
Section: Effects Of Zrf 4 and Hff 4 On Demineralisation Of Dental Harmentioning
confidence: 93%